Diversity and Community Structure of Butterflies (Lepidoptera: Papilionoidea) in The Sigolo-Golo Tourism Area, Jombang, East Java - WIbisana, Oki Rahmatirta; Zumar, Muhammad Rifqi; Ahmad Alfin, Romzalis; Muhamad Azmi Dwi, Susanto (Hasanuddin University, 2024)
The Sigolo-golo natural tourism area is located in the Wonosalam district, Jombang. The environment in this area is still relatively well preserved because it has a variety of vegetation and habitats. There is very little information on the community structure of butterflies (Papilionoidea) in this area, so this research is needed to find the community structure of butterflies in Sigolo-golo tourism. The method used in this research is a visual encounter survey combined with the transect method, which is to carry out direct counts of species and individuals of butterflies that are often found. The research locations were divided based on different habitat types, namely plantations, forests, and riverbanks. This study found 43 species with 358 individuals from five families. The results of the data analysis show that the diversity index value at each location is in the high category. The diversity and revealing butterflies at each location explain why the community structure in Sigolo-golo tourism is still stable and well maintained.